PENGARUH PAJAK DAERAH DAN RETRIBUSI DAERAH TERHADAP PENDAPATAN ASLI DAERAH KOTA SURABAYA - Hariz, Miftahul; Priyono, Joko (widya balina, 2025)
This study aims to analyze the influence of local taxes and levies on Surabaya City's Original Regional Revenue (PAD) during the 2014–2024 period. PAD is a crucial indicator for measuring regional fiscal independence, so understanding the factors influencing it is highly relevant. This study employed a quantitative approach using secondary data in the form of revenue realization reports obtained from the Directorate General of Taxes and Finance (DJPK) of the Ministry of Finance and the Surabaya Regional Revenue Agency (Bapenda). Multiple linear regression analysis was used to determine the partial and simultaneous effects of both independent variables on PAD. Descriptive results indicate that local taxes have experienced stable long-term growth, despite a decline during the pandemic. While local levies tend to fluctuate and are more dependent on the level of public service activity. Through statistical testing, this study is expected to identify the contribution of each variable to increasing PAD and provide strategic recommendations for local governments in optimizing revenue. The findings also provide an empirical overview that can be used as a basis for planning more effective and sustainable regional fiscal policies.